Fabrication, structural and vibrational properties, and physical and optical properties tailoring of nanocrystalline MoS2 films. Issue 15 (15th October 2019) - Xie, Ruishi; Li, Yuanli; Huang, Heyan; Hu, Hailong; Li, Tongcai; Guo, Baogang; Su, Li; Zhang, Xingquan; Xu, Guangliang; Wang, Lielin; Chi, Fangting; Liu, Haifeng; et al.
Abstract: The modification and tuning features of nanostructured films are of great interest because of controllable and distinctive inherent properties in these materials. Here, nanocrystalline MoS2 films were fabricated on the stainless steels by a radio frequency magnetron sputtering at ambient temperature. X-ray photoelectron spectroscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and Raman scattering spectroscopy were used to study the chemical state, chemical composition, crystal structure and vibrational properties of the fabricated MoS2 films. The bias voltage dependent structural evolution and its influence on the optical properties of MoS2 nanocrystalline films were systematically investigated. Besides, the residual stresses of MoS2 nanocrystalline films were explored by employing sin 2 ψ approach. X-ray diffraction demonstrates that the nanocrystalline MoS2 films have single-phase hexagonal crystal structure. All MoS2 films are polycrystalline in nature. The bandgap values are found to be intensively dependent on bias voltage. Our findings show that the nanocrystalline MoS2 films with different physical properties and intense quantum confinement effect can be realized through adjusting bias voltages. This work may provide deep insight for realizing transitional metal dichalcogenide-based nanostructured film optoelectronic devices with tunable physical properties through a traditional, very cost-effective, and large-scale fabrication method.